The impact of the work ethic in the organizational excellence An Empirical Study of Public Administration and Rasheed Bank branches - Mohammad hussain aljonabi; Saad abid aber (Iraqi Journal for Administrative Sciences, 2025)
Work ethic has become an organizational resource of paramount importance in achieving organizational excellence, and business organizations seeking to consolidate these ethics in organizational culture and requiring workers to the outward ethics distinct formulas determine proper handling of customer relationship management. Have been identified for the purposes of this research work ethic as the direction of management and behavior towards employees and customers, and has to do with the organization within the community, as well as the relationship with the laws and government legislation and classifications The organizational excellence, it points above the levels of knowledge that reflect the performance of employees and the organization and achieve their goals and relationships with others held in and the customer in particular. The research sample deliberate of (39) staff in the Department workforce and AL-Rasheed Bank branches For the purposes of statistical and Mathematical analysis has been addressed (26) questionnaire was obtained from the sample and the analysis showed a statistically significant relationship splash and work ethics of the unexamined organizational excellence as well as the analysis specific and personal to members of the sample has research found that the results of the work is the most important factor of organizational excellence and the focus of banking management, which stresses the need for the nomination and the development of concepts of justice and public welfare departments in the bank subsidiary and the insurance regulatory climate to achieve this.